2016
DOI: 10.1016/j.biopsych.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Acid Sensing Regulates Carbon Dioxide-Evoked Fear

Abstract: Background Carbon dioxide (CO2) inhalation, a biological challenge and pathological marker in Panic Disorder, evokes intense fear and panic attacks in susceptible individuals. The molecular identity and anatomical location of CO2-sensing systems that translate CO2-evoked fear remains unclear. We investigated contributions of microglial acid sensor T cell death associated gene-8 (TDAG8) and microglial pro-inflammatory responses in CO2-evoked behavioral and physiological responses. Methods CO2-evoked freezing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 54 publications
15
76
0
Order By: Relevance
“…Previous reports of CO 2 inhalation in rats have reported freezing behavior using a similar concentration (Mongeluzi et al, 2003). 10% CO 2 also evokes freezing in mice as reported by our group (Vollmer et al, 2016), and others (Ziemann et al, 2009; Taugher et al, 2014, Liebold et al, 2016). Thus CO 2 -evoked immobility/freezing behavior appears to be consistent across species and strains and likely represents a fear-associated defensive behavior.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous reports of CO 2 inhalation in rats have reported freezing behavior using a similar concentration (Mongeluzi et al, 2003). 10% CO 2 also evokes freezing in mice as reported by our group (Vollmer et al, 2016), and others (Ziemann et al, 2009; Taugher et al, 2014, Liebold et al, 2016). Thus CO 2 -evoked immobility/freezing behavior appears to be consistent across species and strains and likely represents a fear-associated defensive behavior.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, orexin neurons in the lateral hypothalamic area are CO 2 -senstive and are relevant to the behavioral and physiological effects of CO 2 inhalation (Johnson et al, 2012). In recent studies, our lab reported regulation of CO 2 -evoked fear by microglial acid sensing mechanisms (Vollmer et al, 2016). It will be important to tease out contributions of these targets to differential CO 2 sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second analysis of the same regions was performed to determine morphological differences in microglia, as previously described (Vollmer et al, 2016). Briefly, acquired images were analyzed using ImageJ software to quantify soma area and microglial process complexity and length (ramification).…”
Section: Methodsmentioning
confidence: 99%
“…They also express receptors that allow them to sample the extracellular milieu of the brain. For example, in this issue of Biological Psychiatry , research by Vollmer et al suggests that microglia detect the acidotic conditions triggered by carbon dioxide exposure through the acid-sensing receptor T-cell death–associated gene-8 (4). Microglia are also sensitive to neuronal activity that is driven by sensory stimuli transmitted from the external world.…”
Section: Modern Perspectives On Microglial Function: Neuronal Homeostatsmentioning
confidence: 99%